Preparation, characterization and application of polymeric ultra-permeable biodegradable ferromagnetic nanocomposite adsorbent for removal of Cr(VI) from synthetic wastewater: kinetics, isotherms and thermodynamics - Suter, Evans; Rutto, Hilary; Makomere, Robert; Banza, Musamba; Seodigeng, Tumisang; Kiambi, Sammy; Omwoyo, Wesley (Frontiers in Environmental Chemistry, 2024)
This study explored the feasibility of employing a novel polymeric ferromagnetic nanocomposite adsorbent made of low-cost, biodegradable, and ultra-permeable materials from pulp and paper sludge for adsorptive removal of hexavalent chromium (Cr 6+ ) from synthetic wastewater. Vibrating-sample magnetometer (VSM), X-ray diffraction (XRD), scanning electron microscopy (SEM), Brunauer-Emmet-Teller surface area (BET), and Fourier transform infrared (FTIR) were used to analyze the produced nanocomposite adsorbent. The FTIR results confirmed the presence of adsorptive peaks attributed to -OH, -NH2, and FeO. SEM micrographs revealed a porous adsorbent surface. XRD revealed the existence of the crystalline spinel-structured magnetite (Fe3O4) phase of iron oxide, while the saturation magnetization was established to be 26.90 emu/g. The BET analysis confirmed a slight decrease in the surface area of the nanocomposite adsorbent to 6.693 m 2 .g -1 , compared to Fe3O4 (7.591 m 2 .g -1 ). The optimum conditions for Cr 6+ removal were pH 2.0, 1.0 g/L adsorbent dose, room temperature (25 °C), 120 minutes of contact time, and 20 mg/L pollutant concentration. During removal, the Cr(VI) was adsorbed by electrostatic attraction and/or reduced to trivalent chromium Cr(III). At low starting Cr(VI) concentrations, chemisorption dominated the removal process, but as concentrations increased, physisorption became more significant. The prepared nanocomposite adsorbent presented exceptional removal efficiency of up to 92.23%, indicating that it may be useful for the adsorption of metal ions from industrial and household wastewater.